Creative engagement with migration. Issue 1 (1st April 2019) - Jeffery, Laura; Palladino, Mariangela; Rotter, Rebecca; Woolley, Agnes
This article introduces a special issue on arts-based engagement with migration, comprising articles, reflections, poems and images. The introductory article starts by exploring the ethical, political and empirical reasons for the increased use of arts-based methods in humanities and social sciences research in general, and in migration studies in particular. Next, it evaluates participatory methods, co-production and co-authorship as increasingly well-established practices across academia, the arts, activism and community work. It then considers how the outputs of such processes can be deployed to challenge dominant representations of migration and migrants. The authors reflect critically upon arts-based methodological practices and on the (limits to the) transformative potentials of using arts-based methods to engage creatively with migration. Sounding a cautionary note, they concede that even collaborative artistic expressions have limits in overcoming unequal power dynamics, conveying experiences of migration and effecting long-term change in a context in which discourse on migration is dominated by short-term political decision-making, and punitive policies force migrants into precarious forms of existence. While the prospect of influencing the political sphere might seem remote, they advocate for the role and power of the arts in instigating, shaping and leading change by inspiring people's conscience and civic responsibility.